All about flooble | fun stuff | Get a free chatterbox | Free JavaScript | Avatars
 perplexus dot info

 Just prove it (Posted on 2013-10-20)
Prove that:
If (x+sqrt{1+y^2})*(y+sqrt{1+x^2})=1,
then
x+y=0 .

 No Solution Yet Submitted by Ady TZIDON No Rating

Comments: ( Back to comment list | You must be logged in to post comments.)
 Hyperbolic Approach Comment 4 of 4 |
Anything to avoid those square roots...

Let x = sinh(2X)  and y = sinh(2Y), so that the equation becomes

[sinh(2X) + cosh(2Y)] [sinh(2Y) + cosh(2X)] = 1

cosh(2X)cosh(2Y)+sinh(2X)sinh(2Y)+sinh(2X)cosh(2X)+sinh(2Y)cosh(2Y)=1

cosh(2X + 2Y) + 0.5 sinh(4X) + 0.5 sinh(4Y) = 1

cosh2(X + Y) + sinh2(X + Y) + sinh(2X + 2Y)cosh(2X – 2Y) = 1

2 sinh2(X + Y) + 2 sinh(X + Y)cosh(X + Y)cosh(2X –2Y) = 0

sinh(X + Y) [sinh(X + Y) + cosh(X + Y)cosh(2X –2Y)] = 0   (1)

Since cosh(X + Y) >= 1 and cosh(2X – 2Y) >= 1 for all X, Y,
the expression in square brackets >=  sinh(X + Y) + cosh(X + Y)
= exp(X + Y)
> 0
So the only solution from (1) is:  sinh(X + Y) = 0 which gives X = -Y.
Since sinh is an odd function, it follows that sinh(2X) = -sinh(2Y) and
therefore that x + y = 0.

 Posted by Harry on 2013-10-28 08:48:51
Please log in:
 Login: Password: Remember me: Sign up! | Forgot password

 Search: Search body:
Forums (0)
Newest Problems
Random Problem
FAQ | About This Site
Site Statistics
New Comments (6)
Unsolved Problems
Top Rated Problems
This month's top
Most Commented On

Chatterbox:
Copyright © 2002 - 2018 by Animus Pactum Consulting. All rights reserved. Privacy Information